Anxiety’s level of bantenes patient’s: the effect of dhikr therapy before surgical procedure - Wulandari, Indah; Huriyati, Aty (International Journal of Research in Medical Sciences, 2017)
Background: Anxiety is a subjective feeling which people’s feels when they faced a surgical procedure. Spirituality approach such as, dhikr can be used to reduce patient’s anxiety, especially when they are facing a medical-surgical procedure. In Banten, dhikr is an act of worship that people did, especially when they will under-taken the medical-operation. The purpose of this study was to determine the effect of dhikr therapy to the decreasing of anxiety level of patients with pre-operative procedure. Methods: The research design was quasi-experiment without control-goup, and have measure the pre-operative patient’s anxiety before and after dhikr therapy. Statistical analysis by using dependent paired t-test. Samples from this study were patients who pre-operative appendictomy procedure with the total number 23 respondents that were selected by using purposive technique. Anxiety level was measured by using Hamilton Anxiety Rating Scale. Results: The results of this research showed that there was found the effect of dhikr therapy to the decreasing of anxiety of pre-operative’s patient with p value = 0.000, and the mean score before intervention is 3.13, while after intervention was 1.49. Conclusions: In conclusion, anxiety can affect a person’s health in particular who will undergo surgery. Anxiety can be reduced by one of them is religious approach as dhikr. With routine of dhikr someone will get a peace of mind. The inner peace will reduce the impact of stress hormones that are released when a person feels anxious.